2017
DOI: 10.1007/s40368-017-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of paediatric oral biopsies over a 10-year period in Western India

Abstract: The majority of lesions identified were of a benign nature necessitating minimal intervention; however, it is important to recognise that malignant lesions can occur in children. Any swelling, especially related to the salivary glands, must be investigated immediately, so as to prevent mortality and reduce morbidity. Diverse classifications used by previous authors make comparison of data challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Cross-sectional studies are important in estimating the prevalence of OC and in identifying highrisk individual. In this study, the male:female ratio was (1.04:1), slight male predominance had been noticed, agree with studies (Cavalcante et al, 2016, Ha et al, 2014and Patil et al, 2017, and disagree with Taweevisit et al (2018) and Ambika et al (2011) both showed slight female predominance. The prevalence of oral conditions in this study was 54.4% which was higher than reported in the nearby countries such as Turkey (26.2 %) (Parlak et al, 2006) and Iran (28%) (Jahanfar et al, 2012), possibly because the sample of the current study was from a dental center and not from general hospital, beside; high number of subjects was examined, but it was lower than a study done in India (Ambika et al, 2011), in which 1003 children 4-14 years were included in the study, the prevalence was 64.11%.…”
Section: Discussionsupporting
confidence: 70%
“…Cross-sectional studies are important in estimating the prevalence of OC and in identifying highrisk individual. In this study, the male:female ratio was (1.04:1), slight male predominance had been noticed, agree with studies (Cavalcante et al, 2016, Ha et al, 2014and Patil et al, 2017, and disagree with Taweevisit et al (2018) and Ambika et al (2011) both showed slight female predominance. The prevalence of oral conditions in this study was 54.4% which was higher than reported in the nearby countries such as Turkey (26.2 %) (Parlak et al, 2006) and Iran (28%) (Jahanfar et al, 2012), possibly because the sample of the current study was from a dental center and not from general hospital, beside; high number of subjects was examined, but it was lower than a study done in India (Ambika et al, 2011), in which 1003 children 4-14 years were included in the study, the prevalence was 64.11%.…”
Section: Discussionsupporting
confidence: 70%
“…The 6% prevalence of paediatric cases in our study was comparable with that of previous surveys of paediatric oral lesions carried out by dental facilities in different countries (see Table 4). These studies reported that~10% of specimens submitted for pathology examination come from children [1][2][3]5,7,8,14,16 . A slight female predominance was observed in the present study, in contrast to no gender predilection or a slight male predominance in these other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Oral lesions in children show a spectrum which differs from that in adults, being related to growth and development, as well as specific lesions that predominate in the paediatric age group, such as vascular tumours and some types of lymphoma 1,2 . Previous studies regarding the prevalence of oral lesions in children have been based on retrospective review of pathology reports published from different regions of the world, including Argentina, Australia, Brazil, Chile, India, Nigeria, Turkey, Taiwan and Thailand, the UK and the USA [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . In total, 2.8-16.2% of specimens come from patients in the paediatric age group, depending on the age cut-off used to define a paediatric patient 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the qualitative analysis of this study, the age group proved to be an important modifying factor in the prevalence of oral malignancies 14 . There was a significant variation in the patients' age ranges, such as ≤12 years old 29,53 or ≤20 years old 16,19,30,36 .…”
Section: Resultsmentioning
confidence: 62%